History and theater, archive and performance: tentacular temporality in Um pássaro não é uma pedra [A Bird Is Not a Stone] (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
For this article, an analysis was carried out of the play A Bird Is Not a Stone, a solo performance by Lucas Oradovschi, which premiered in Rio de Janeiro in 2024. Drawing on formal choices in staging and dramaturgy, the analysis examined the play as a means of bringing the history of theatre to the stage as a performative practice of inquiry and cross-temporal “contracena”. The research was informed by reenactment studies, considering the dynamics of mutual activation between archive and performance, and explored the idea of ‘tentacular temporality’ for this scene as a means of engagement, knowledge production and experience of a historical moment of theatre in Palestine.
Keywords: Reenactment; Stone Theatre; Freedom Theatre; Theatre in Palestine